My3s (Malaysian Soft Skills Scale) Strategies for Soft Skills Development Through the Fostering of Entrepreneurial Skills: An Analysis - Rashidi, Abbas; Fakhrul Adabi, Abdul Kadir; Ilhamie, Abdul Ghani Azmi (Universiti Malaysia Pahang, 2013)
This study is done to look into the formation of 'human capital' among students of Higher Leaming Institutes in Malaysia, through the fostering of entrepreneurial skills. The study sample of 480 first degree students from the sixth semester are taken from the Malaysian Technical University Network or MTUN comprising of Universiti Malaysia Pahang (UMP), Universiti Teknikal Malaysia Melaka (UTeM), Universiti Tun Hussein Onn (UTHM) and Universiti Malaysia Perlis (UNiMAP). In the meantime, researchers have used the three-layer group sampling. Then, the study data were analysed using the Statistical Package for Social Sciences (SPSS) version 19.0 in order to obtain the value of the mean, standard deviation and Pearson's Correlation. The study outcome points to the moderately strong relationship, significant between the value of trust with the mastery of entrepreneurial skills.Meanwhile, accountability shows a very strong significance with the entrepreneurial skills. Finally, the study outcome demonstrates the level of mastery of students' entrepreneurial skills remains at a high level. All in all, this study concludes that there exists a significant correlation between the human capital with the mastery of entrepreneurial skills which needs to be given due attention to elevate the performance of the university and students' potential.